Comprehensive insights into biological and bio-electrochemical treatment of the sago industry wastewater: Challenges and future perspectives - Subramaniapillai Niju; V. Shruthi; K. Priyadharshini (Sustainable Chemistry for the Environment)
The food industrial sector holds a crucial position, as it satisfies the basic human need for sustenance while contributing to economic growth. Within this sector, the sago industry plays a vital role in the small-scale industrial sector and contributes to the local economy. However, the processing of tapioca roots requires a large quantity of water and simultaneously generates a large volume of the wastewater. The wastewater generated is highly organic in nature, which poses a serious threat to the environment if untreated. Conventional treatment methods are highly expensive and struggle to effectively manage the high pollutant load. So, there is a need for sustainable and cost-efficient treatment options. Biological treatment methods, particularly use of anaerobic processes, along with aerobic methods, are highly effective in reducing Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD) in sago wastewater because of its organic Content. However, these methods face enormous challenges, such as the need for the optimized operational conditions when dealing with varying wastewater compositions. In context to that the bioelectrochemical system, MFCs offers a sustainable approach by combining wastewater treatment along with bioelectricity generation. Use of this technique is highly advantageous, including improved COD removal and energy recovery. At the same time, they face some of the notable challenges, including scalability of the system performance. This review provides detailed knowledge on the characteristics nature of the sago wastewater and highlights the importance of biological treatment methods, pinpointing on aerobic and anaerobic treatments, as well as bio-electrochemical systems, emphasizing their role in COD removal and power generation.